2020
DOI: 10.3390/jmse8010025
|View full text |Cite
|
Sign up to set email alerts
|

Circulation in the Gulf of Khambhat—A Lagrangian Perspective

Abstract: The circulation of the Gulf of Khambhat (GoK) is studied from a Lagrangian point of view using a 2D numerical model. The model-predicted tide elevation and current speed are in agreement with the observations. Seasonal variations of advection of particles are simulated by releasing 237 particles homogeneously distributed over the Gulf. After one month of simulation, no particles escaped from the GoK except a few from the southern GoK during southwest monsoon (June–September), and the advection of particles was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 26 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…The GoKB is characterized by a funnel-shaped indentation, shallow depth (maximum 30 m), and a large tidal flat. The Lagrangian modeling studies showed that the particles released into the Gulf do not leave the system except for a few particles from the south of the region, suggesting restricted water-mass exchange between the Gulf and the AS (Mitra et al, 2020). Gujarat accounts for around 65% of the total plastic production of India.…”
Section: Potential Accumulation Zones In the Indian Seasmentioning
confidence: 99%
“…The GoKB is characterized by a funnel-shaped indentation, shallow depth (maximum 30 m), and a large tidal flat. The Lagrangian modeling studies showed that the particles released into the Gulf do not leave the system except for a few particles from the south of the region, suggesting restricted water-mass exchange between the Gulf and the AS (Mitra et al, 2020). Gujarat accounts for around 65% of the total plastic production of India.…”
Section: Potential Accumulation Zones In the Indian Seasmentioning
confidence: 99%